Kepahitan Hidup Maryam dalam Kisah Al-Qur’an - Masykuroh, Siti; Yana, Rina; Isnaeni, Ahmad; Masruchin, Masruchin (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2023)
AbstractMaryam Binti Imran is a revered female who Allah selected as the only female sanctified by Him and the best female. Allah tried Maryam during the period of her life that is chronicled in the Qur'anic narrative because it is so bitter. The study aims to shed light on Maryam's life stages throughout her lifetime. This study is descriptive and analytical through pure literature, focusing on discussing bitter moments in Maryam's life as described in the Qur'an. According to the study's findings, Maryam's long period of bitterness was an effort on Allah's part to get her ready to share in His Majesty. The first step in the preparation was accepting her mother's vow and selecting Zakaria as her best caregiver, who taught her about taqwa and preserving her purity. Allah's extensive preparations for the birth of the extraordinary figure known as Isa was aimed at Maryam's pregnancy and her extraordinary labor.Keywords: Maryam; Quranic story; Tribulation. AbstrakMaryam Binti Imran adalah sosok seorang perempuan langit yang dipilih Allah sebagai perempuan terbaik dan menjadi satu satunya perempuan yang disucikan oleh Allah. Bentangan kehidupan Maryam sebagaimana digambarkan dalam kisah al-Qur’an begitu sarat dengan kepahitan, Allah mengujinya dengan kepahitan hidup. Penelitian ini bertujuan untuk mengungkap fase-fase kehidupan Maryam semasa hidupnya. Kajian ini bersifat deskriptif analitis melalui kepustakaan murni, yang menfokuskan bahasan pada episode-episode kepahitan dalam bentangan kehidupan Maryam sebagaimana dikisahkan dalam al-Qur’an. Temuan penelitian ini menyimpulkan bahwa bentangan kepahitan yang dihadapi Maryam adalah cara Allah mempersiapkan Maryam untuk menjadi sebagian dari tanda kebesaran-Nya. Persiapan dimulai sejak diterima-Nya nadzar sang ibunda dan dipilihnya pengasuh terbaik-Zakaria- yang mengajarkannya tentang taqwa dan terjaganya kesucian pribadinya. Kehamilan Maryam dan persalinan yang luarbiasa adalah tujuan dari semua persiapan panjang yang Allah bentangkan untuk lahirnya sosok luar biasa yaitu Isa.Kata Kunci: Kepahitan Hidup; Kisah Al-Qur’an; Maryam.